Crossing the Digital Divide: A Review of Literature on Information and Communication Technology Usage in Schools - Albalawi, Fahad (Technium Social Sciences Journal, 2021)
This review of literature explores research in multiple areas that are relevant to the implementation of information and communication technology (ICT) use in school districts in Saudi Arabia. This review examines the national priorities in Saudi Arabia and their relevance to ICT usage in education. This review also highlights the research-based rationale for using ICT in education, including its benefits to teachers and students. In addition, this review examines both the individual and systemic barriers to ICT implementation, especially as these barriers may inform our understanding of the barriers present in Saudi Arabian schools. For the same reason, this review discusses potential solutions to these challenges. Additional themes discussed include the use of ICT in e-learning, a need for teacher training in ICT, and a need for support from the Ministry of Education. A particular emphasis is placed on Tearle’s (2004) A Theoretical and Instrumental Framework for Implementing Change in ICT in Education, as this framework provides a useful and appropriate framework for future study. Keywords Information and communication technology (ICT), e-learning, teacher training, education in Saudi Arabia, digital divide